Fiction and the Ontological Landscape - Thomas G. Pavel (Studies in 20th & 21st Century Literature, 1981)
The paper examines fictional ontologies in relation to the distinction between sacred and profane ontologies. This distinction suggests that most cultures organize their worldview into various ontological landscapes. Several types of such landscapes are examined and fiction is characterized as a peripheral ontology used for ludic and instructional purposes.
Keywords: ontological landscape; fiction; fictional ontologies; cultures; cultural worldviews; peripheral ontology; ludic; being; meaning